Prospective association between objective measures of childhood motor coordination and sedentary behaviour in adolescence and adulthood - Lee Smith; Abigail Fisher; Mark Hamer (2015)
Background Higher levels of gross motor coordination are positively associated with physical activity in childhood, but little is known about how they relate to sedentary behaviour. The aim of this study was to investigate the longitudinal association between gross motor coordination at childhood and sedentary behaviour in adolescence and adulthood. Methods Data were from the 1970 British Cohort Study (the age 10, 16, and 42-year surveys). At age 10 the participant’s mother provided information on how often participants watched TV and played sports and a health visitor administered several tests to assess gross motor coordination. At aged 16 and 42-years participants reported their daily screen and TV time, respectively, and physical activity status. We examined associations between gross motor coordination at age 10 with sedentary behaviour and physical activity at age 16 and 42, using logistic regression. Results In multivariable models, higher levels of gross motor coordination were associated with lower odds of high screen time (n = 3073; OR 0.79, 95 % CI 0.64, 0.98) at 16-years although no associations with physical activity were observed (OR 1.16, 95 % CI 0.93, 1.44). Similar associations were observed with TV time in adulthood when participants were aged 42, and in addition high gross motor coordination was also associated with physical activity participation (n = 4879; OR 1.18, 95 % CI 1.02, 1.36). Conclusions Intervention efforts to increase physical activity participation and reduce sedentary behaviour over the life course may be best targeted towards children with low gross motor coordination.